THE RELATIONSHIP BETWEEN PEER PRESSURE AND SELF-ESTEEM IN ADOLESCENTS - Levina Nailah; Novca Rahmadani; Aidah Icha; Alfi Ziyana; Novi Noerhayati; Ummi Masrufah Maulidiyah (P3I UMSurabaya, 2025)
Adolescence is a period of significant transition marked by rapid changes in the body, emotions, and social life. During this time, adolescents face many challenges such as academic stress, peer pressure, family conflicts, and social demands, all of which can affect their mental health and overall well-being (Stecz et al., 2020; Kaur et al., 2022). Peer pressure is a major factor that can lead to risky behavior, social isolation, and low self-esteem (Helfert & Warschburger, 2013; Blakemore, 2019; Chung et al., 2021). Self-esteem plays an important role in helping adolescents cope with social and emotional pressures. Adolescents with high self-esteem typically have a positive view of themselves and life, while those with low self-esteem are more likely to feel anxious, depressed, and helpless (Marsh et al., 2004; Das et al., 2016; Peng et al., 2021; Preston & Rew, 2022). Therefore, understanding the relationship between peer pressure and self-esteem is important for comprehensively supporting adolescents' mental health.